MOLECULAR METHODS OF CHARACTERIZATION AND IDENTIFICATION OF GLOBODERA ROSTOCHIENSIS AND GLOBODERA PALLIDA POPULATIONS - Podlewska-Przetakiewicz, Anna; Milczarek, Dorota (Plant Breeding and Seed Science, 2020)
The cyst nematodes belonging to the genus Globodera are big worldwide problem in countries were Sola-naceaous plants growing. Knowledge of species-composition in populations of Globodera rostochiensis and Globodera pallida is very important for selection of appropriate measure of nematode regulations occurrence. Inter- and intraspecific variability among species of Globodera rostochiensis and Globodera pallida were studied intensively with the use of molecular analyses of DNA methods. This review summarize and compare of methods chosen to distinguishing between Globodera, both pathotypes and species.